Sureśvara's Vārtika on Madhu Brāhmaṇa - Sureśvara, ācārya ca. 7./8. Jh. (Advaita tradition series, 1988)
Critical study of a supercommentary on chapter 2, section 5 (Madhu Brāhmaṇa) of Br̥hadāraṇyakopaniṣad, Hindu philosophical classic